DIABETIC KETOACIDOSIS WITH MELIOIDOSIS: A CASE REPORT - Hamizi, Nur Syafiqah; Tang, Jia Jian; Lee, Qiao Yun; Koh, Mia Tuang; Nathan, Anna Marie; Yaakop, Siti Zarina; Jalaludin, Muhammad Yazid; Zaini, Azriyanti Anuar; Samingan, Nurshadia (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION/BACKGROUND Paediatric melioidosis is uncommon yet is associated with high morbidity and mortality in severe disease particularly in immunocompromised patients. Reports of melioidosis in paediatric diabetes are scarce. We present two patients with melioidosis who presented with diabetic ketoacidosis (DKA) in our centre. CASE Patient A is a 15 year-9-month-old female with underlying type 1 diabetes (T1D). She presented with mild DKA (serum glucose: 25 mmol/L, serum ketone: 3.9 mmol/L venous pH: 7.30, HCO3 - : 13 mmol/L) associated with fever and symptoms of upper respiratory tract infection (URTI) for 4 days. She remained febrile despite 2 courses of intravenous (IV) amoxicillin-clavulanic acid and oral erythromycin. A chest radiograph at day 9 of illness showed collapsed consolidation of the left upper lobe of the lung. She was noted to have hepatosplenomegaly on physical examination at day 12. Abdominal ultrasound revealed multiple well-defined splenic microabscesses. Routine blood and respiratory cultures were negative, but serum IgM titres for melioidosis were positive. She was treated with IV meropenem and oral trimethoprim-sulfamethoxazole. Patient B is a 12-year-old female who presented with prolonged fever and newly diagnosed DKA (serum glucose: 30.3 mmol/L, serum ketone: 3.5 mmol/L venous pH: 7.24, HCO3 - : 12.6 mmol/L). Her fever persisted despite DKA resolution. She developed septic shock needing intensive care admission due to severe pneumonia with bilateral pleural effusion. CT thorax and abdomen showed consolidated changes in the lungs and multiple abscesses in the liver and spleen. Blood cultures grew Burkholderia pseudomallei which confirmed melioidosis infection. She was treated with 6 weeks of IV ceftazidime, meropenem and trimethoprim-sulfamethoxazole. CONCLUSION Prolonged fever in children presenting with DKA must be thoroughly investigated. Melioidosis is uncommon, however, it needs to be ruled out to ensure adequate treatment of patients with immunocompromised status.